İstanbul metropolitan municipality and environment through the perspective of the eu - İkizer, İhsan (My University, 2007)
Türkiye’nin Avrupa Birliği ile olan müzakere sürecindeki en zorlu fasıllardan biri çevredir ve bu faslın Türkiye’deki uygulayıcısı, tıpkı AB üyesi ülkelerde olduğu gibi, belediyelerdir. Türkiye’nin en eski ve en büyük belediyesi olarak yaklaşık 50.000 çalışanı ile 14 milyon insana hizmet veren İstanbul Büyükşehir Belediyesi (İBB), Türkiye’de çevre alanındaki en önemli uygulayıcıdır. Bu çalışmada, İBB’nin çevre alanında sunmuş olduğu hizmetler, İBB’nin ilgili birimlerinden elde edilen faaliyet raporları ve diğer belgeler yoluyla, AB çevre mevzuatı perspektifinden değerlendirilmiştir. İBB’nin çevre alanında çok sayıda başarılı olarak kabul edilebilecek hizmete ve yatırıma imza attığı gözlenmiştir; ancak, AB çevre standartlarına tam olarak uyum sağlayabilmesi için İBB’nin kat etmesi gereken uzun bir yol vardır.

Environment is one of the most challenging chapters in the negotiations process of Turkey with the European Union and the main implementer of this chapter is municipalities in Turkey as it is in the EU member countries. Istanbul Metropolitan Municipality (IMM), which is the greatest and the oldest local authority in Turkey, with around 50.000 employees serving for around 14 million people, is one of the most important implementing actors in Turkey, concerning environment. In this study, Istanbul Metropolitan Municipality has been examined with regards to its services in the area of environment through the perspective of the European Union's relevant legislation, thanks to activity reports and other documents of the relevant departments of IMM. It was observed that IMM undersigned many services and investments in the area of environment, which might be accepted as successful; however, it needs to exert more and more efforts to fully conform to the EU environmental standards.
Keywords: Atık Yönetimi; Avrupa Birliği; Çevre; Gürültü; Kirlilik